Genetic Analysis and Molecular Mapping of an All-Stage Stripe Rust Resistance Gene in Triticum aestivum-Haynaldia villosa Translocation Line V3 - Lu HOU; Dong-fang MA; Mao-lin HU; Miao-miao HE; Yan LU; Jin-xue JING (Journal of Integrative Agriculture)
Triticum aestivum-Hayaldia villosa translocation line V3 has shown effective all-stage resistance to the seven dominant pathotypes of Puccinia striiforms f. sp. tritici prevalent in China. To elucidate the genetic basis of the resistance, the segregating populations were developed from the cross between V3 and susceptible genotype Mingxian 169, seedlings of the parents and F2 progeny were tested with six prevalent pathotypes, including CYR29, CYR31, CYR32-6, CYR33, Sun11-4, and Sun11-11, F1 plants and F3 lines were also inoculated with Sun11-11 to confirm the result further. The genetic studied results showed that the resistance of V3 against CYR29 was conferred by two dominant genes, independently, one dominant gene and one recessive gene conferring independently or a single dominant gene to confer resistance to CYR31, two complementary dominant genes conferring resistance to both CYR32-6 and Sun11-4, two independently dominant genes or three dominant genes (two of the genes show cumulative effect) conferring resistance to CYR33, a single dominant gene for resistance to Sun11-11. Resistance gene analog polymorphism (RGAP) and simple-sequence repeat (SSR) techniques were used to identify molecular markers linked to the single dominant gene (temporarily designated as YrV3) for resistance to Sun11-11. A linkage map of 2 RGAP and 7 SSR markers was constructed for the dominant gene using data from 221 F2 plants and their derived F2:3 lines tested with Sun11-11 in the greenhouse. Amplification of the complete set of nulli-tetrasomic lines of Chinese Spring with a RGAP marker RG1 mapped the gene on the chromosome 1B, and then the linked 7 SSR markers located this gene on the long arm of chromosome 1B. The linkage map spanned a genetic distance of 25.0 cM, the SSR markers Xgwm124 and Xcfa2147 closely linked to YrV3 with genetic distances of 3.0 and 3.8 cM, respectively. Based on the linkage map, it concluded that the resistance gene YrV3 was located on chromosome arm 1BL. Given chromosomal location, the reaction patterns and pedigree analysis, YrV3 should be a novel gene for resistance to stripe rust in wheat. These closely linked markers should be useful in stacking genes from different sources for wheat breeding and diversification of resistance genes against stripe rust.